The Effect of Work Experience, Job Satisfaction and Work Discipline On Working Achievement with Job Placement as Intervening Variables on PT. Ramayana Lestari Sentosa Tbk. Sidoarjo - Andriani, Dewi; Anggraeni, Dita Listyana; Putra, Joni Johanda; Rosiana, Monica (Faculty of Economics and Business, Jenderal Soedirman University, 2022)
This study aims to determine the effect of Experience, Satisfaction, and Work Discipline on Job Performance and the influence of Experience, Satisfaction, and Work Discipline on Job Performance with Placement as an Intervening Variable at PT Ramayana Lestari Sentosa Tbk. The approach used in this research is quantitative. The population in this study was 250 employees. This research used non probability sampling especially purposive sampling. The sample in this study was 96 respondents—analyzed using SmartPLS 3.0 software. The results show that experience, satisfaction, and work discipline have a significant effect on work performance, experience has a significant effect on job performance, satisfaction has a significant effect on job performance, and discipline has a significant effect on job performance. In addition, the results show that experience, satisfaction, and work discipline significantly affect job performance through job placement as an intervening variable.